Revolutionary brotherhood : Freemasonry and the transformation of the American social order, 1730-1840 - Bullock, Steven C.; Institute of Early American History and Culture (Williamsburg, Va.) (Chapel Hill : University of North Carolina Press, 1996)
"In the first comprehensive history of the fraternity known to outsiders primarily for its secrecy and rituals. Steven Bullocks traces Freemasonry through its first century in America. He follows the order from its origins in Britain and its introduction into North America in the 1730s to its near-destruction by a massive anti-Masonic movement almost a century later and its subsequent reconfiguration into the brotherhood we know today. With a membership that included Benjamin Franklin, George Washington, Paul Revere, and Andrew Jackson. Freemasonry is fascinating in its own right, but Bullock also places it at the center of the transformation of American society and culture from the colonial era to the rise of Jacksonian democracy." "Using lodge records, members' reminiscences and correspondence, and local and Masonic histories. Bullock links Freemasonry with the changing ideals of early American society."--Jacket
I. The Lodge of InstructionII. The Rugged Road; III. The Thick Veil; Part Four. Masonry and Democracy; Chapter Ten: The Lion and the Crows: Antimasonry, 1826-1840; I. The Concentration of Great Numbers on a Single Point; II. A Stupendous Mirror; III. These Desperate Fanatics; Epilogue. Losing the Right to Reverence: Masonry's Decline and Revival; A Note on Masonic Sources; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z.
Includes bibliographical references (pages 321-405) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Freemasonry -- United States -- History -- 18th century; Freemasonry -- United States -- History -- 19th century; Franc-maçonnerie -- États-Unis -- Histoire -- 18e siècle.; Franc-maçonnerie -- États-Unis -- Histoire -- 19e siècle.; HISTORY -- United States -- Revolutionary Period (1775-1800); SOCIAL SCIENCE -- General; Freemasonry; United States; Freimaurer; USA; Vrijmetselarij; Geschichte 1730-1840.; 1700-1899; History